2021
DOI: 10.1007/s10278-021-00463-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Localization of Endotracheal Tube on Chest Radiographs Using a Cascaded Convolutional Neural Network Approach

Abstract: Rapid and accurate assessment of endotracheal tube (ETT) location is essential in the intensive care unit (ICU) setting, where timely identification of a mispositioned support device may prevent significant patient morbidity and mortality. This study proposes a series of deep learning-based algorithms which together iteratively identify and localize the position of an ETT relative to the carina on chest radiographs. Using the open-source MIMIC Chest X-Ray (MIMIC-CXR) dataset, a total of 16,000 patients were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 18 publications
1
27
1
Order By: Relevance
“…Deep learning (DL) has been widely used in image processing since the successful application of CNNs to image classification and object recognition (12). Various DL approaches have been applied to many different aspects of CXR, ranging from image quality control ( 13) and detection of the orientation of CXR images (14,15) to more complicated applications, such as anatomic segmentation (16,17), disease classification (18)(19)(20)(21)(22), and ETT detection (23)(24)(25)(26)(27). Several reports have been published for automated detection of the ETT on CXR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning (DL) has been widely used in image processing since the successful application of CNNs to image classification and object recognition (12). Various DL approaches have been applied to many different aspects of CXR, ranging from image quality control ( 13) and detection of the orientation of CXR images (14,15) to more complicated applications, such as anatomic segmentation (16,17), disease classification (18)(19)(20)(21)(22), and ETT detection (23)(24)(25)(26)(27). Several reports have been published for automated detection of the ETT on CXR.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity was only 66.5% and specificity 99.2% when assessing ETT-carina distance 7 cm. Using the open-source MIMIC Chest X-Ray dataset and 3 CNN algorithms, Kara et al (25) reported the accuracy, sensitivity, specificity, PPV, NPV, and AUC of 97.14%, 97.37%, 96.89%, 97.12%, 97.15%, and 99.58% respectively, upon a five-fold cross-validation to classify the presence or absence of the ETT, and the model-predicted locations of the carina and the distal tip of ETT were estimated having a median error of 0.46 cm and 0.60 cm from manual groundtruth annotations, respectively. Harris et al (26) trained a bounding box-based CNN for localization of the ET tube and the carina, with a mean difference of 0.7 cm between the model-predicted ETT-carina distance and the ground-truth measurement agreed by two experienced radiologists in 200 CXR images.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we also provide results on a large scale proprietary dataset of over 100K chest X-ray images. Our method inspired by the OOOE assumption outperforms two commonly used baselines: (1) a simple segmentation model [23,26] and (2) a regression based detection approach [15]. We additionally demonstrate that our approach leads to a model that generalizes better across datasets and makes better use of global context information.…”
Section: Introductionmentioning
confidence: 74%
“…Regression based approaches such as [15] are trained by directly minimizing the mean-square-error (MSE) between the predicted location g(X) = ŷreg ∈ R 2 and the ground truth location y as depicted in (a) of Figure 1.…”
Section: Point Detection Headmentioning
confidence: 99%
See 1 more Smart Citation